Proyecto de inversión para la creación de un centro de estimulación temprana en la ciudad de Macará Provincia de Loja - Saquicela Sanmartín, Magaly Susana (2016)
The research was conducted in the City of Macará, whose overall objective was to conduct a "INVESTMENT PROJECT FOR THE CREATION OF AN EARLY STIMULATION CENTRE CITY MACARÁ Loja Province," the same that it met the specific objectives; they were raised and aimed at developing the investment project. For the study of market surveys was necessary to run 370 to 4,831 Macarenas families, and thus meet the needs of this city, and obtaining supply and unmet demand, and the company logo and the trade name was also performed called "little feet". To prepare the technical study, you must know the size, location and project engineering for a suitable working environment and provide quality service, the company in the first year working with 80% of its capacity, the same that will be located on the road between Carlos Veintemilla Abdon Calderon and Carlos Ramón, mission, vision, principles, values and flow chart of the establishment registration was developed. In the center of early stimulation el-legal administrative, study in which the structural and functional organization chart was prepared, which served as the basis for manual functions applied each department, in which contains the legal framework, regulations and labor obligations for each employee. With the completion of the financial assessment, optimal elements for its implementation was discussed in detail, with the required investment of $ 38,315.78 to implement early learning center, reaching to determine that the project is feasible because a NPV was obtained $ 74.471,20 greater than 0; the project IRR is 84,17% higher than the interest rate; Capital recovery is 1 year, 1 months and 16 days; Benefit Cost Ratio in this case will be invested each pain will have $ 1.40 of profit; and is 0.99 Sensitivity Analysis indicates that this is in the acceptance limits of the project and will support an increase in the cost of 23,15% over its lifetime. With the application of the methodology used allowed the development of the proposed project, highlighting the techniques, the calculation of 5 sample size and the general description of each of the parts of the research At the end conclusion arises as the lack of a center of stimulation that helps children 0-3 years to develop their skills. And Recommendation is to create the early learning center that has all the necessary services for child care, this service would provide excellent quality, specialized professionals and thus meet the needs of parents